Key regulatory challenges in developing modified new chemical drugs in China: a national survey study - Fu, Lixia; Jia, Guoshu; Wei, Minji; Cui, Yimin (Frontiers in Pharmacology, 2025)
ObjectiveWith the increasing number of modified new chemical drugs (MNCDs) entering the market or in the approval pipeline in China, understanding their current status is crucial. This study aims to present stakeholders’ perspectives on the R&D and regulatory challenges associated with MNCDs.MethodsA nationwide online survey was conducted to collect perspectives from industrial stakeholders involved in drug R&D, drug manufacturing, and contract research organizations (CROs) and other related fields. A web-based questionnaire link was distributed to pharmaceutical professionals via the social media platform “WeChat”. Data were analyzed using descriptive statistics.ResultsA total of 362 participants from 178 organizations across 19 provinces in China were recruited. Half of the respondents had over 10 years of work experience, 66% held intermediate or higher professional titles, and over 90% were experienced in R&D or regulatory submissions. Most respondents identified clinical advantage evaluation as the primary regulatory hurdle, with the lack of clear guidance and case references cited as significant impediments in the R&D and marketing application of MNCDs. Furthermore, clinical trial efficacy and safety data were identified as the main factors influencing the successful market launch of MNCDs, with expert consultation being the predominant method for assessing clinical advantages.ConclusionDespite the issuance of several guidance for MNCDs, the industry still faces regulatory challenges in assessing the clinical advantages of these drugs. Additionally, there is a need for more objective and clear guidance in the R&D of modified new drugs. These findings are critical for regulators to refine the regulatory framework of MNCDs.